A Grave Complex of the Early Single Grave Culture at Skarrild Overby, Central Jutland - Rostholm, Hans (Journal of Danish Archaeology, 1982)
A Grave Complex of the Early Single Grave Culture at Skarrild Overby, Central Jutland